2000
DOI: 10.1095/biolreprod62.3.511
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Antigen 6 Is the Murine Homologue of the Chlamydomonas reinhardtii Central Apparatus Protein Encoded by the PF16 Locus1

Abstract: A cDNA encoding sperm antigen 6 (Spag6), the murine homologue of the Chlamydomonas reinhardtii PF16 protein-a component of the flagella central apparatus-was isolated from a mouse testis cDNA library. The cDNA sequence predicted a 55.3-kDa polypeptide containing 8 contiguous armadillo repeats with 65% amino acid sequence identity and 81% similarity to the Chlamydomonas PF1 protein. An antipeptide antibody generated against a C-terminal sequence recognized a 55-kDa protein in sperm extracts and localized Spag6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
69
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 21 publications
6
69
0
1
Order By: Relevance
“…Identity was 30-40% between human and trypanosome orthologues, with the exception of PF16, which was more than 60% identical. These values are in the same range as between Chlamydomonas and human flagellar genes (Pennarun et al, 1999;Sapiro et al, 2000). By contrast, the PFR genes, initially identified in T. brucei (Deflorin et al, 1994;Schlaeppi et al, 1989), are exclusively present in trypanosomatid and euglenid genomes so far with no counterpart in other species (Kohl and Bastin, 2005).…”
Section: Identification and Rnai Silencing Of Trypanosome Axoneme Genesmentioning
confidence: 55%
“…Identity was 30-40% between human and trypanosome orthologues, with the exception of PF16, which was more than 60% identical. These values are in the same range as between Chlamydomonas and human flagellar genes (Pennarun et al, 1999;Sapiro et al, 2000). By contrast, the PFR genes, initially identified in T. brucei (Deflorin et al, 1994;Schlaeppi et al, 1989), are exclusively present in trypanosomatid and euglenid genomes so far with no counterpart in other species (Kohl and Bastin, 2005).…”
Section: Identification and Rnai Silencing Of Trypanosome Axoneme Genesmentioning
confidence: 55%
“…Scale bars in electron micrographs are 50 nm. the homologue of the Chlamydomonas PF16 locus encoding a protein of the central apparatus of the axoneme (Neilson et al 1999, Sapiro et al 2000, 2002. Easy sperm decapitation was also reported in mice with Oaz-t (Oaz3) deficiency, the testis-specific ornithine decarboxylase antizyme, presumably by affecting the local concentration of polyamines (Tokuhiro et al 2009).…”
Section: Discussionmentioning
confidence: 97%
“…Additional sequence information concerning the human cDNA will be needed to determine whether this is the human version of the PF6 gene; however, its expression in the testis is consistent with a potential flagellar function. Interestingly, recent studies have demonstrated that several of the central pair polypeptides first characterized in Chlamydomonas have closely related (i.e., 60 -70% identity) vertebrate homologues Lefebvre, 1996, 1997;Neilson et al, 1999;Sapiro et al, 2000).…”
Section: Composition and Structure Of Central Pair Projectionsmentioning
confidence: 99%
“…Additional sequence information concerning the human cDNA will be needed to determine whether this is the human version of the PF6 gene; however, its expression in the testis is consistent with a potential flagellar function. Interestingly, recent studies have demonstrated that several of the central pair polypeptides first characterized in Chlamydomonas have closely related (i.e., 60 -70% identity) vertebrate homologues Lefebvre, 1996, 1997;Neilson et al, 1999;Sapiro et al, 2000).The large size of the PF6 protein (Ͼ238 kDa) and its sedimentation characteristics on sucrose density gradients (ϳ12.6S) suggest that the PF6 polypeptide may serve as a molecular scaffold for the assembly of components associated with the 1a projection on the C1 microtubule. The pf6 mutations result in the absence of the C1-1a projection (Figures 1 and 2) and the loss of two or more polypeptides that appear to cosediment with the PF6 protein ( Figure 9B).…”
mentioning
confidence: 99%